Preparation method and application of boron-nitrogen modified metal electrocatalyst for improving oxygen reduction durability

Through boron and nitrogen modification technology, the problem of poor durability of precious metal catalysts in oxygen reduction reaction is solved, and the durability of precious metal electrocatalysts is improved and the electrocatalytic performance optimization is achieved. It is suitable for fuel cells.

CN114665110BActive Publication Date: 2025-04-01DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210122919.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-09
Publication Date
2025-04-01
Estimated Expiration
2042-02-09

AI Technical Summary

Technical Problem

The poor durability of precious metal catalysts in oxygen reduction reactions limits the commercial application of fuel cells.

Method used

Through boron-nitrogen modification technology, materials such as ammonia borane complex are combined with precious metal electrocatalysts to form boron-nitrogen-modified precious metal electrocatalysts (BN-PtM/C) to improve their oxygen reduction durability.

Benefits of technology

The noble metal electrocatalyst modified by boron nitrogen shows significant durability improvement in the oxygen reduction reaction, maintaining high stability and good electrocatalytic performance, while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003499236070000011
    Figure HDA0003499236070000011
  • Figure HDA0003499236070000012
    Figure HDA0003499236070000012
  • Figure HDA0003499236070000021
    Figure HDA0003499236070000021
Patent Text Reader

Abstract

The present invention relates to a preparation method and application of a boron-nitrogen modified metal electrocatalyst for improving oxygen reduction durability, and belongs to the field of fuel cell electrocatalyst materials. The preparation method is: disperse the noble metal electrocatalyst in a solvent, stir evenly to obtain a black solution, add NH3-BH3 to the solution, wait until the bubbles completely disappear, dry, and obtain a mixture of white powder and black powder. Carbonize the mixture under argon conditions. The present invention is simple to operate for preparing the noble metal electrocatalyst modified by boron-nitrogen, has fewer processes, less equipment investment, good repeatability, and is easy to solve the problem of difficulty in large-scale production. It can also provide a new protection strategy for other types of electrocatalysts and electrocatalyst carriers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a boron-nitrogen modified metal electrocatalyst for improving oxygen reduction durability, and belongs to the field of fuel cell electrocatalyst materials. Background Art

[0002] Since the Industrial Revolution, the demand for fossil energy has been affecting human production and life, and some new energy sources have emerged, such as fuel cells, metal-air batteries, etc. Oxygen reduction reaction plays a very important role in these new energy devices. At present, precious metal catalysts are considered to be the best oxygen reduction electrocatalysts for fuel cells, but their scarcity, high recycling costs and poor durability have hindered their large-scale commercial application. Especially in terms of durability, the ability to maintain the high stability of precious metal catalysis is urgently needed for current commercial electrocatalysts. Therefore, it is imperative to rationally design a low-cost, abundant substance to improve the durability of precious metal electrocatalysts.

[0003] Boron nitride (BN) is a class of compounds with special chemical and physical properties. Boron nitride is a crystal composed of nitrogen atoms and boron atoms. The chemical composition is 43.6% boron and 56.4% nitrogen, with four different variants: hexagonal boron nitride (h-BN), rhombohedral boron nitride (r-BN), cubic boron nitride (c-BN) and wurtzite boron nitride (w-BN). In recent years, boron nitride has been used in many fields and has become an emerging research field, especially in the field of corrosion, which can greatly improve the corrosion resistance of the original materials. Among them, hexagonal boron nitride is considered to be the best crystal form for improving durability. However, hexagonal boron nitride is an insulator and does not conduct electricity. If it is coated on a precious metal catalyst, it will affect the conductivity of the precious metal and ultimately affect the electrocatalytic activity of the metal. Summary of the invention

[0004] In order to find anti-poisoning materials for precious metal electrocatalysts and completely get rid of dependence on imported products, mature commercial raw materials are selected from the cost point of view, and the raw materials are processed to protect the performance of precious metal electrocatalysts and prevent them from being poisoned. The present invention provides a method and application of a boron-nitrogen modified precious metal electrocatalyst for improving oxygen reduction durability with a simple process and environmental friendliness. The presence of some hexagonal boron nitride can not only maintain the stability of the catalyst's catalytic activity but also take into account the conductivity of the catalyst itself.

[0005] The first object of the present invention is to provide a method for preparing a boron-nitrogen modified metal electrocatalyst for improving oxygen reduction durability.

[0006] A method for preparing a boron-nitrogen modified noble metal electrocatalyst for improving oxygen reduction durability comprises the following steps:

[0007] (1) The noble metal electrocatalyst is dissolved in a solvent, and then ammonia borane complex (NH3-BH3), triethylamine borane ((C2H5)3N-BH3), trimethylamine borane (C3H9N-BH3), dimethylamino borane (C2H 10 BN), dicyclohexylamine borane (BH3-C 12 H 23 N) or borane-tert-butylamine complex (BH3-C4H 11 N), placed in a fume hood, and allowed to stand for 12 to 36 hours, until no bubbles are generated in the solution, ultrasonicated for 5 to 30 minutes to form a stable black slurry, then magnetically stirred in a constant temperature water bath at 25 to 100° C. for 12 to 36 hours, and then dried at the same temperature for 12 to 36 hours to obtain a black and white mixed product after evaporation;

[0008] (2) The black and white mixed products are carbonized under argon conditions to obtain a boron-nitrogen modified noble metal electrocatalyst for future use, denoted as BN-PtM / Cm (where m is the mass ratio of the ammonia borane complex (NH3-BH3) to the noble metal electrocatalyst (PtM / C)).

[0009] Among them, the ammonia borane complex, triethylamine borane ((C2H5)3N-BH3), trimethylamine borane (C3H9N-BH3), dimethylamino borane (C2H 10 BN), dicyclohexylamine borane (BH3-C 12 H 23 N) or borane-tert-butylamine complex (BH3-C4H 11 N) and the ratio of solvent is 1-600 mg: 1-200 mL, preferably 50 mg: 100 mL; ammonia borane complex, triethylamine borane ((C2H5)3N-BH3), trimethylamine borane (C3H9N-BH3), dimethylamino borane (C2H 10 BN), dicyclohexylamine borane (BH3-C 12 H 23 N) or borane-tert-butylamine complex (BH3-C4H 11 The mass ratio of N) to the noble metal electrocatalyst is 1-600:1-500, preferably 50:25-100, more preferably 50:50.

[0010] The solvent is water, methanol, ethanol or diethylene glycol dimethyl ether.

[0011] Furthermore, in step (1), the noble metal electrocatalyst comprises a noble metal (active substance) and a carrier, the noble metal is platinum, palladium or gold, and the loading amount of the noble metal is 20-60wt%, for example, 20, 37, 40, 60wt% Pt / C can be used.

[0012] Furthermore, in step (1), the molecular weight of the ammonia borane complex (NH3-BH3) is 30.87 g / mol, and the purity is 97%.

[0013] Furthermore, in step (1), during the preparation of the mixed solution of the ammonia borane complex and the noble metal electrocatalyst, the ammonia borane complex (NH3-BH3), triethylamine borane ((C2H5)3N-BH3), trimethylamine borane (C3H9N-BH3), dimethylamine borane (C2H 10 BN), dicyclohexylamine borane (BH3-C 12 H 23 N) or borane-tert-butylamine complex (BH3-C4H 11 The ratio of N) to the noble metal electrocatalyst and the solvent is 1-600 mg: 1-500 mg: 1-200 mL, preferably 50 mg: 25-100 mg: 100 mL, and more preferably 50 mg: 50 mg: 100 mL.

[0014] Furthermore, in step (1), the ammonia borane complex is preferably better combined with the noble metal electrocatalyst to form a uniform black and white blended product. The stirring reaction conditions are: keeping warm at 50-100°C for 12-36 hours, more preferably keeping warm at 90°C for 12 hours.

[0015] Further, in step (2), the carbonization conditions of the black and white blended products are: in an argon atmosphere, the temperature is increased to 200-1000°C at a heating rate of 1°C / min-5°C / min, kept warm for 1-6 hours, and then cooled to room temperature with the furnace, which is recorded as BN-PtM / CmT (where T is the holding temperature). Preferably, the carbonization conditions of the present invention are: in an argon atmosphere, the temperature is increased to 500°C at a heating rate of 5°C / min, kept warm for 1-6 hours, and then cooled to room temperature with the furnace, which is recorded as BN-PtM / Cm-500. Most preferably, the carbonization conditions are: in an argon atmosphere, the temperature is increased to 500°C at a heating rate of 5°C / min, and kept warm for 2 hours.

[0016] Furthermore, in step (2), the black and white mixed products are carbonized under argon conditions, and the obtained product is washed, dried and ground to obtain a boron-nitrogen modified noble metal electrocatalyst.

[0017] Further, in step (2), the washing is an acid washing, and the obtained product is soaked in 1-8 mol / L nitric acid (HNO3) solution for 1-12 hours, then centrifuged with deionized water to neutrality, and then washed with anhydrous ethanol by centrifugation; the centrifugation condition is: centrifugation at 5000r / min-10000r / min for 2-10min. Preferably, the acid washing activation of the present invention is: the obtained product is soaked in 1-8 mol / L HNO3 solution, centrifuged with deionized water at 8000r / min for 5min, repeatedly centrifuged until neutrality, and then washed with anhydrous ethanol by centrifugation at 8000r / min for 5min. Further, the present invention preferably uses 2 mol / L HNO3 solution.

[0018] Furthermore, in step (2), the drying conditions after washing are: drying at 50-100° C. for 12-36 hours, and a forced air drying oven can be used for drying.

[0019] Another object of the present invention is to provide a boron-nitrogen modified metal electrocatalyst prepared by the above method for improving the durability of oxygen reduction, which also provides a reference for improving the durability of other electrocatalysts.

[0020] After the boron nitrogen modified metal electrocatalyst of the present invention is modified by boron nitrogen, its original particle size does not undergo obvious growth or agglomeration, and the original particle size is well maintained, with the particle size maintained at: 2.1±0.5nm, with uniform size, and the particles are evenly supported on the carbon surface.

[0021] Another object of the present invention is to provide the use of the above-mentioned boron-nitrogen modified metal electrocatalyst as a fuel cell cathode catalyst material, which significantly improves durability.

[0022] The present invention removes part of the hydrogen of the ammonia borane complex (NH3-BH3) in an aqueous solution through the catalysis of a noble metal catalyst, dissolves it, dries it, recrystallizes it, and attaches it to the surface of the noble metal. The obtained mixture powder is carbonized under argon conditions, and the obtained product is washed, dried, and ground to obtain.

[0023] The present invention carefully combines ammonia borane complexes with precious metals. The original precious metals and carbon carriers are protected by boron nitrogen. Under the premise of not affecting conductivity, some hexagonal boron nitride will appear when boron nitrogen is subjected to high temperature, thereby protecting the precious metal electrocatalyst from poisoning. The constructed boron nitrogen-modified precious metal electrocatalyst makes up for the lack of durability often encountered in the field of electrocatalysis.

[0024] The present invention contains more nitrogen and boron elements through ammonia borane complex. Boron nitride is a good corrosion-resistant protective material, and the corrosion resistance of some hexagonal boron nitride is better than that of boron nitride. After one-step pyrolysis, a boron-nitrogen-modified precious metal electrocatalyst (BN-PtM / C) is creatively designed. The appearance of hexagonal boron nitride forms a protective layer on the surface of the carbon carrier in this boron-nitrogen-modified precious metal electrocatalyst. The high-potential anti-reverse pole test protects the carbon carrier from poisoning, indirectly protecting the precious metal particles. The appearance of hexagonal boron nitride also plays an isolating role between the particles, preventing them from agglomerating, thereby affecting the overall oxygen reduction activity of the electrocatalyst. The boron-nitrogen-modified precious metal electrocatalyst also shows good performance and long-term stability as an oxygen electrocatalyst for the cathode of a fuel cell.

[0025] The beneficial effects of the present invention are as follows: the electrocatalyst material prepared by the method of the present invention is a material with high durability and uniform particle size, and has good electrocatalytic performance. The durability of the catalyst is significantly improved by a cheap material. In addition, the present method can also be used for reference in other commercial electrocatalysts. The method of preparing boron-nitrogen-modified noble metal electrocatalysts of the present invention is simple to operate, has fewer processes, less equipment investment, and good repeatability, which is convenient for solving large-scale production problems, and also provides new options and protection strategies for other types of electrocatalysts (such as palladium, gold and other noble metals) that are easy to be poisoned. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 (ad) are TEM images of the BN-PtM / C sample prepared in Example 1 of the present invention at different magnifications (wherein the scale bar in (a) is 100 nm, the scale bar in (b) is 50 nm, the scale bar in (c) is 20 nm and the scale bar in (d) is 10 nm).

[0027] Figure 2 It is the XRD spectrum of the boron nitrogen supported carbon (BN-C) prepared in Comparative Example 2 of the present invention.

[0028] Figure 3 (a) and (b) are the XPS B1s and N1s spectra of BN-PtM / C prepared in Example 1, respectively.

[0029] Figure 4 (a) is the cyclic voltammetry curve of the BN-PtM / C prepared in Examples 1 to 6 of the present invention and the PtM / C oxygen reduction electrocatalyst material prepared in Comparative Example 1 under acidic conditions, Figure 4 (b) is the polarization curve of the BN-PtM / C prepared in Examples 1 to 6 of the present invention and the PtM / C oxygen reduction electrocatalyst material prepared in Comparative Example 1 at 1600 rpm under acidic conditions.

[0030] Figure 5 (a) is the cyclic voltammetry curve of the BN-PtM / C oxygen reduction electrocatalyst prepared in Example 1 of the present invention after 30,000 potentiodynamic scans under acidic conditions, Figure 5 (b) is the polarization curve of the BN-PtM / C oxygen reduction electrocatalyst prepared in Example 1 of the present invention at 1600 rpm after 30,000 potentiodynamic scans under acidic conditions.

[0031] Figure 6 (a) is a line graph of the electrochemically active specific surface area (ECSA) of the cyclic voltammetry curve of the BN-PtM / C oxygen reduction electrocatalyst prepared in Example 1 of the present invention after 30,000 potentiodynamic scans under acidic conditions, Figure 6 (b) is a line graph of the mass specific activity (MA) of the BN-PtM / C oxygen reduction electrocatalyst prepared in Example 1 of the present invention after 30,000 potentiodynamic scans at 1,600 rpm under acidic conditions.

[0032] Figure 7 (a) is the invention Figure 6 (a) Normalized ECSA of treatments, Figure 7 (b) is the present invention Figure 6 (b) Processed normalized MA. DETAILED DESCRIPTION

[0033] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0034] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0035] Example 1

[0036] 1) Take 50 mg of noble metal electrocatalyst (37 wt % of commercial platinum carbon, manufacturer: Johnson Matthey), add 100 mL of deionized water, stir evenly, and obtain a black slurry.

[0037] 2) Add 25 mg of NH3-BH3 (CAS No.: 13774-81-7, Aladdin) to the solution, let it stand for 12 hours, wait until the bubbles disappear completely, ultrasonicate for 15 minutes, place it in a 60°C constant temperature water bath with magnetic stirring for 12 hours, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a mixture of white powder and black powder.

[0038] 3) The mixture was carbonized in a tubular furnace with argon gas. The carbonization procedure was as follows: heating from room temperature to 500°C at a heating rate of 5°C / min, keeping warm for 2 hours, then cooling to room temperature with the furnace, taking out, and grinding with an agate mortar for 1 minute without washing or drying. It was recorded as BN-PtM / C-2 (m is the mass ratio of PtM / C to NH3-BH3).

[0039] 4) The catalyst was tested for RDE (rotating disk electrode) performance in a standard three-electrode electrochemical cell under acidic conditions (0.1M HClO4). The glassy carbon electrode with the catalyst was used as the working electrode, the graphite rod was used as the counter electrode, and saturated calomel was used as the reference electrode in the acidic system. The catalyst loading on the electrode provided in Example 1 was 10 μg / cm 2 All potentials in the present invention are RHE potentials. A 20 wt % Pt / C electrocatalyst was used as a control, and its loading was 10 μg Pt cm -2 The test was carried out in N2-saturated or O2-saturated 0.1M HClO4 aqueous solution at 25°C. -1 The cyclic voltammetry (CV) curve of the catalyst was tested under the conditions of rotation rate of 1600 rpm and positive scan rate of 10 mV·s -1 The catalyst electrochemical test conditions in Examples 2-7 and Comparative Example 1 are the same as those in Example 1.

[0040] Example 2

[0041] 1) Take 50 mg of noble metal electrocatalyst (37 wt % of commercial platinum carbon, manufacturer: Johnson Matthey), add 100 mL of deionized water, stir evenly, and obtain a black slurry.

[0042] 2) Add 50 mg of NH3-BH3 (CAS No.: 13774-81-7, Aladdin) to the solution, let it stand for 12 hours, wait until the bubbles disappear completely, ultrasonicate for 15 minutes, place it in a 60°C constant temperature water bath with magnetic stirring for 12 hours, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a mixture of white powder and black powder.

[0043] 3) The mixture was carbonized in a tubular furnace with argon gas. The carbonization procedure was as follows: heating from room temperature to 500°C at a heating rate of 5°C / min, keeping the temperature for 2 hours, then cooling to room temperature with the furnace, taking out, and grinding with an agate mortar for 1 minute without washing or drying. It was recorded as BN-PtM / C-1.

[0044] Example 3

[0045] 1) Take 50 mg of noble metal electrocatalyst (37 wt % of commercial platinum carbon, manufacturer: Johnson Matthey), add 100 mL of deionized water, stir evenly, and obtain a black slurry.

[0046] 2) Add 75 mg of NH3-BH3 (CAS No.: 13774-81-7, Aladdin) to the solution, let it stand for 12 hours, wait until the bubbles disappear completely, ultrasonicate for 15 minutes, place it in a 60°C constant temperature water bath with magnetic stirring for 12 hours, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a mixture of white powder and black powder.

[0047] 3) The mixture was carbonized in a tubular furnace with argon gas. The carbonization procedure was as follows: heating from room temperature to 500°C at a heating rate of 5°C / min, keeping the temperature for 2 hours, then cooling to room temperature with the furnace, taking out, and grinding with an agate mortar for 1 minute without washing or drying. It was recorded as BN-PtM / C-2 / 3.

[0048] Example 4

[0049] 1) Take 50 mg of noble metal electrocatalyst (37 wt % of commercial platinum carbon, manufacturer: Johnson Matthey), add 100 mL of deionized water, stir evenly, and obtain a black slurry.

[0050] 2) Add 100 mg of NH3-BH3 (CAS No.: 13774-81-7, Aladdin) to the solution, let it stand for 12 hours, wait until the bubbles disappear completely, ultrasonicate for 15 minutes, place it in a 60°C constant temperature water bath with magnetic stirring for 12 hours, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a mixture of white powder and black powder.

[0051] 3) The mixture was carbonized in a tubular furnace with argon gas. The carbonization procedure was as follows: heating from room temperature to 500°C at a heating rate of 5°C / min, keeping the temperature for 2 hours, then cooling to room temperature with the furnace, taking out, and grinding with an agate mortar for 1 minute without washing or drying. It was recorded as BN-PtM / C-1 / 2.

[0052] Example 5

[0053] 1) Take 50 mg of noble metal electrocatalyst (37 wt % of commercial platinum carbon, manufacturer: Johnson Matthey), add 100 mL of deionized water, stir evenly, and obtain a black slurry.

[0054] 2) Add 100 mg of NH3-BH3 (CAS No.: 13774-81-7, Aladdin) to the solution, let it stand for 12 hours, wait until the bubbles disappear completely, ultrasonicate for 15 minutes, place it in a 60°C constant temperature water bath with magnetic stirring for 12 hours, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a mixture of white powder and black powder.

[0055] 3) The mixture was carbonized in a tubular furnace with argon gas. The carbonization procedure was as follows: heating from room temperature to 500°C at a heating rate of 5°C / min, keeping the temperature for 2 hours, then cooling to room temperature with the furnace, taking out, and grinding with an agate mortar for 1 minute without washing or drying. It was recorded as BN-PtM / C-1 / 3.

[0056] Example 6

[0057] 1) Take 50 mg of noble metal electrocatalyst (37 wt % of commercial platinum carbon, manufacturer: Johnson Matthey), add 100 mL of deionized water, stir evenly, and obtain a black slurry.

[0058] 2) Add 100 mg of NH3-BH3 (CAS No.: 13774-81-7, Aladdin) to the solution, let it stand for 12 hours, wait until the bubbles disappear completely, ultrasonicate for 15 minutes, place it in a 60°C constant temperature water bath with magnetic stirring for 12 hours, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a mixture of white powder and black powder.

[0059] 3) The mixture was carbonized in a tubular furnace with argon gas. The carbonization procedure was as follows: heating from room temperature to 500°C at a heating rate of 5°C / min, keeping the temperature for 2 hours, then cooling to room temperature with the furnace, taking out, and grinding with an agate mortar for 1 minute. No washing or drying was required. The mixture was recorded as BN-PtM / C-1 / 4.

[0060] Comparative Example 1

[0061] 1) Take 50 mg of noble metal electrocatalyst (37 wt % of commercial platinum carbon, manufacturer: Johnson Matthey) and place it in a crucible.

[0062] 2) Carry out carbonization treatment in a tubular furnace with argon gas. The carbonization procedure is as follows: heat from room temperature to 500°C at a heating rate of 5°C / min, keep warm for 2 hours, then cool to room temperature with the furnace, take out, and grind with an agate mortar for 1 minute without washing or drying. It is recorded as PtM / C.

[0063] Comparative Example 2

[0064] 1) Take 50 mg of commercial carbon black EC600 (manufacturer: Akzo Nobel), add 100 mL of deionized water, stir evenly to obtain a black slurry.

[0065] 2) Add 50 mg of NH3-BH3 (CAS No.: 13774-81-7, Aladdin) to the solution, let it stand for 12 hours, wait until the bubbles disappear completely, ultrasonicate for 15 minutes, place it in a 60°C constant temperature water bath with magnetic stirring for 12 hours, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a mixture of white powder and black powder.

[0066] 3) The mixture was carbonized in a tubular furnace with argon gas. The carbonization procedure was as follows: heating from room temperature to 500°C at a heating rate of 5°C / min, keeping the temperature for 2 hours, then cooling to room temperature with the furnace, taking out, and grinding with an agate mortar for 1 minute without washing or drying. It was recorded as BN-C.

[0067] Effect example: In order to explore the morphological characteristics and electrochemical properties of the prepared BN-PtM / Cm electrocatalyst, TEM, XRD, XPS, Raman and other methods were used to physically characterize the prepared products, and the products were prepared into electrodes to test the corresponding electrochemical properties.

[0068] Figure 1 (ad) are TEM images of the BN-PtM / C-2 catalyst prepared in Example 1 (wherein the scale bar in (a) is 100 nm, the scale bar in (b) is 50 nm, the scale bar in (c) is 20 nm, and the scale bar in (d) is 10 nm). It can be seen from the TEM images in the figure that the particles are dispersed more evenly, and the size of the precious metal nanoparticles is small, with a size of 2.1±0.5 nm; Figure 1 As can be observed in (d), the sample modified with boron and nitrogen did not show any particle growth phenomenon, which did not affect the electrocatalytic performance.

[0069] Figure 2 This is the XRD spectrum of BN-C prepared in Comparative Example 2. After carbonization treatment at 500° C., the peaks of boron nitride appear including (002), (101), and (110).

[0070] Figure 3 (a) and (b) show the N1s and B1s spectra of XPS of BN-PtM / C-2 prepared in Example 1, respectively. Figure 3 (a) is a high-resolution N1s spectrum, from which the presence of BN can be clearly observed. In addition, it also contains a small amount of O-BN. Figure 3 (b) is a high-resolution B1s spectrum, from which we can conclude that boron exists in the form of BN or even h-BN.

[0071] Figure 4(a) is the cyclic voltammetry curve of the BN-PtM / C prepared in Examples 1 to 6 of the present invention and the PtM / C oxygen reduction electrocatalyst material prepared in Comparative Example 1 under acidic conditions; Figure 4 It can be seen from (a) that in the cyclic voltammetry curves of electrocatalyst materials with different ratios in 0.1M HClO4 aqueous solution, as the ratio increases, the limiting current density shows a decreasing trend; Figure 4 (b) is the polarization curve of the BN-PtM / C prepared in Examples 1 to 6 of the present invention and the PtM / C oxygen reduction electrocatalyst material prepared in Comparative Example 1 at 1600rpm under acidic conditions; It can be seen from Figure 4 (b) that in the polarization curves of electrocatalyst materials with different proportions in 0.1M HClO4 aqueous solution, as the proportion increases, the limiting current density shows a decreasing trend, and the starting potential and half-wave potential also show a decreasing trend, but when the ratio is between 2:1 and 1:2, the electrocatalyst is still active, while the 1:3 and 1:4 electrocatalysts lose their activity.

[0072] Figure 5 (a) is the cyclic voltammetry curve of the BN-PtM / C-2 oxygen reduction electrocatalyst material prepared in Example 1 of the present invention after 30,000 potentiodynamic scans under acidic conditions; Figure 5 As can be seen from (a), in a 0.1M HClO4 aqueous solution, as the number of dynamic potentiostatic scans increases, the limiting current density of the cyclic voltammetry curve decreases accordingly. Figure 5(b) is the polarization curve of the BN-PtM / C-2 oxygen reduction electrocatalyst prepared in Example 1 of the present invention at 1600rpm after 30,000 dynamic potentiostatic scans under acidic conditions; Figure 5 As can be seen in (b), in 0.1M HClO4 aqueous solution, as the number of potentiodynamic scans increases, the electrochemical performance decreases, and its corresponding starting potential and half-wave potential decrease, and then tend to be stable.

[0073] Figure 6 (a) is based on Figure 5 (a) Calculated electrochemically active specific surface area (ECSA) (implemented in accordance with national standard GB / T20042.4-2009); Figure 6 As can be seen in (a), the initial ECSA can reach 130.71 mA / mg PGM , after 30,000 potential scans, it can still reach 105.49mA / mg PGM . Figure 6 (b) is based on Figure 5 (b) The converted mass specific activity (MA), Figure 6 (b) is based on Figure 5(b) The mass specific activity (MA) obtained by conversion is based on the formula 1 / i = 1 / i k +1 / i d , find i k ,i d is the limiting diffusion current density; i k is the kinetic current density; i is the current density at 0.9V; then calculate MA according to the following formula, the unit is mA / mg Pt .from Figure 6 In (b), it can be seen that the initial MA can reach 440.60mA / mg Pt , after 30,000 potential scans, it can still reach 355.73mA / mg Pt .

[0074] Figure 7 (a) is based on Figure 6 (a) The normalized ECSA curve obtained by processing; Figure 7 As can be seen in (a), after 30,000 potentiodynamic scans, the ECSA decayed by 19.25%. Figure 7 (b) is based on Figure 6 (b) The normalized MA curve obtained by processing; Figure 7 As can be seen in (b), after 30,000 potentiodynamic scans, the MA decayed by 19.15%.

Claims

1. A method for preparing a boron-nitrogen-modified metal electrocatalyst for improving oxygen reduction durability, characterized in that: The steps include: (1) dissolving a noble metal electrocatalyst in a solvent, adding an ammonia borane complex, triethylamine borane, trimethylamine borane, dimethylamino borane, dicyclohexylamine borane, or borane-tert-butylamine complex, standing for 5 to 30 minutes until the bubbles disappear completely, stirring at 50 to 100 °C for 12 h to 36 h, and then drying at the same temperature for 12 h to 36 h to obtain a mixture; The noble metal in the noble metal electrocatalyst is platinum, palladium or gold; (2) carbonizing the mixture under argon conditions to obtain a black powder; The ratio of the ammonia borane complex, triethylamine borane, trimethylamine borane, dimethylamino borane, dicyclohexylamine borane, and borane-tert-butylamine complex to the solvent is 50 mg: 100 mL; the mass ratio of the ammonia borane complex, triethylamine borane, trimethylamine borane, dimethylamino borane, dicyclohexylamine borane, and borane-tert-butylamine complex to the noble metal electrocatalyst is 50: 25-100; The solvent is water; In step (2), the carbonization conditions are: in an argon atmosphere, heating to 200-500°C at a heating rate of 1°C / min-5°C / min, keeping the temperature for 1-2h, and then cooling to room temperature in the furnace; Application of boron-nitrogen modified metal electrocatalysts as cathode electrocatalyst materials for fuel cells.

2. The method according to claim 1, characterized in that: In step (1), the loading amount of the noble metal in the noble metal electrocatalyst is 20-60 wt%.

3. The method according to claim 1, characterized in that: In step (2), the carbonization conditions are: under argon atmosphere, heating to 200-500°C at a heating rate of 1°C / min-5°C / min, keeping the temperature for 1-2h, and then cooling to room temperature in the furnace.

4. The method according to claim 1, characterized in that: In step (1), the time for the bubbles to completely disappear is 12 to 36 hours.

5. The method according to claim 1, characterized in that: In step (2), the black mixed product is carbonized under argon conditions, and the obtained product is washed, dried, and ground to obtain a boron-nitrogen modified metal electrocatalyst.

6. The method according to claim 5, characterized in that: In step (2), the washing is as follows: soaking the obtained product in a 1-8 mol / L nitric acid solution for 1-12 h, then centrifuging with deionized water until neutral, and then centrifuging with anhydrous ethanol.

7. The method according to claim 1, characterized in that: The boron-nitrogen modified metal electrocatalyst has uniform size and the particles are uniformly loaded on the surface of the carrier.

Citation Information

Patent Citations

  • Process for producing oxygen reducing catalyst and uses thereof

    US20140178790A1